Incentives for Improving Birth Registration Coverage : A Review of the Literature - World Bank (World Bank, Washington, DC, 2019)
This paper describes a framework of supply and demand factors that could affect birth registration coverage rates, particularly in the context of social transfers. Within this framework, a review of the empirical literature (academic and grey) was conducted on incentives that have been demonstrated to increase birth registration coverage. More than two hundred articles were reviewed, and forty-two (twenty-three academic and nineteen grey) were selected for this study based on relevance. The literature encompassed evidence from Asia, Africa, and Latin America on linking birth registration with social transfer programs, such as cash transfers, which have resulted in increased birth registration rates. The methods in the literature on incentives for countries to increase birth registration coverage vary. There is a lack of scholarly research on incentives to address both supply and demand barriers for birth registration and a need for more robust literature on the topic.